An Approximation of Energy Efficiency in Web Systems - Sola-Morena, Jose M.; Gilly, Katja; Juiz, Carlos (Procedia computer science, 2013)
There is an increasing trend pointing to a responsible and sustainable energy consumption as mandatory in order to decrease the global energy demand more accordingly to the limited non-renewable worldwide energy resources, and consequently, their costs. As a first step, this paper surveys recent studies in literature related to energy efficiency in Web server systems and intends to give a summarised overview and state-of-the-art of the subject for further future contributions in the next- generation. As second step, an energy metric has been implemented and tested in a Web system simulation environment based on the preliminary research of existing methods. The results obtained by the simulations and their discussion are also presented in this paper.